Complex Class 1 Integron in a Clinical Escherichia coli Strain From Vietnam Carrying Both mcr-1 and blaNDM–1 - Le-Vo, Hong-Ngoc; Tran, Phuong Thi-Bich; Le, Lien; Matsumoto, Yuki; Motooka, Daisuke; Nakamura, Shota; Jones, James W.; Iida, Tetsuya; Cao, Van (Frontiers in Microbiology, 2019)
The co-production of MCR and carbapenemase in Enterobacteriaceae has been previously reported. Here, we describe a clinical strain of Escherichia coli from Vietnam carrying both mcr-1 and blaNDM–1. Whole-genome sequencing showed that the genome of this strain consists of a 4,975,832-bp chromosome and four plasmids. The mcr-1 and blaNDM–1 genes are located on IncI2 and IncA/C2-type plasmids, respectively. Genetic analysis revealed the presence of a multidrug-resistant region with the structure of a novel complex class 1 integron including a class 1 integron region bearing two 5′ conserved segments and one 3′ conserved segment and two complete structures of ISCR1. The complex integron contains aminoglycoside resistance genes aadA2, aadB, strA, strB, and aphA6, quinolone resistance gene qnrA1, extended-spectrum β-lactamase gene blaOXA–4, and a Tn125-like transposon bearing blaNDM–1. In addition, the dfrA12-gcuF-aadA2-cmlA1-aadA1-qacH gene cassette array belonging to the sul3-type integron was also identified, but the region found downstream of the gene cassette array is the IS440-tet(M)-IS26 element instead of the sul3 gene. The results further support that Enterobacteriaceae isolates co-harboring mcr and blaNDM are widely being distributed. The structural characteristics of the complex integron reveal that ISCR1 elements play an important role in the mobilization of blaNDM–1 and the development of multidrug-resistant regions.